2022
DOI: 10.1101/2022.09.19.508594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA processing/modifying enzymes play key roles in the response to thermospermine in Arabidopsis thaliana

Abstract: Thermospermine acts in negative regulation of xylem differentiation through enhancing mRNA translation of the members of the SAC51 gene family in Arabidopsis. These mRNAs contain conserved upstream open-reading-frames (uORFs) that are inhibitory to the main ORF translation. To address the mode of action of thermospermine in this process, we have isolated mutants that are insensitive to thermospermine, named its. We show here that four genes responsible for the mutants, its1 to its4, encode a homologue of SPOUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The bHLH transcription factors SAC51, SACL1, and SACL2 that participate in the ACL5-auxin feedback loop are also absent 48 . While SACL3 is retained, PHIP1 49 is lost, which could enhance acl5 dwarfism, producing the “tiny-plant” phenotype found in acl5 sacl3 mutants of Arabidopsis 48 . WOX4 is also absent, which regulates cell division in the procambium 50 , and together with downstream factors such as ATHB-8, likely contributes to the dramatic simplification of the vascular bundle in Lemnaceae 34 .…”
Section: Resultsmentioning
confidence: 99%
“…The bHLH transcription factors SAC51, SACL1, and SACL2 that participate in the ACL5-auxin feedback loop are also absent 48 . While SACL3 is retained, PHIP1 49 is lost, which could enhance acl5 dwarfism, producing the “tiny-plant” phenotype found in acl5 sacl3 mutants of Arabidopsis 48 . WOX4 is also absent, which regulates cell division in the procambium 50 , and together with downstream factors such as ATHB-8, likely contributes to the dramatic simplification of the vascular bundle in Lemnaceae 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Manipulating the PA content in plants by exogenous application or metabolic engineering has shown that PAs are involved in embryogenesis, fruit development and maturation, flower and chloroplast development, organogenesis, and senescence and stress responses. TSpm, for example, controls stem elongation in A. thaliana by promoting the expression of upstream open reading frames (uORFs) that control translation of genes involved in xylem differentiation, which affects stem elongation [ 79 , 144 ]. In fact, some genes required for plant PA biosynthesis are regulated by uORFs, probably in response to specific PAs [ 145 ].…”
Section: A Brief Review Of the Roles Of Polyamines In Plantsmentioning
confidence: 99%